Delivery Style and Listener Response in the Rhythmical Performance of Shakespeare's Sonnets. - Tsur, Reuven (College Literature)
This article is an inquiry into the aesthetic event of the rhythmical performance of poetry. This event typically contains a reciter, a poetic text, and a listener (though the reciter himself may be the listener too). Poetic rhythm is accessible only through some kind of performance, vocalized or silent. Rhythmical performance is not a unitary phenomenon; one must distinguish between various delivery styles. The article aspires to give a fairly comprehensive description of the aesthetic event under the discussion. A pilot experiment suggests that apparently incompatible responses to the same delivery instance may result from the listeners' realization of different subsets of aspects of the same event. They may, therefore, be meaningfully discussed and compared. My assumption is that rhythmical performance and delivery style are determined by the poem's metric structure, the performer's aesthetic conceptions and vocal resources, and the constraints of the cognitive system. I will concentrate on small-scale computer-aided analyses and comparisons of performances by leading British actors. Consequently, I will focus my discussion on recordings of only one line, the last line of Sonnet 129, from commercially-available recordings.